EFEKTIVITAS TERAPI TERTAWA TERHADAP SKOR KECEMASAN MAHASISWA DALAM MENGHADAPI EVALUASI BELAJAR - Eriska, Dessi Widya; ", Herlina "; Utomo, Wasisto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Anxiety was the thing that always be experienced by everyone, especially students in the face of the evaluation study. Theobjective of the research was to determine the effectiveness of Laughter Therapy on Anxiety Level of Students in Facing Evaluation Study. This research used"Quasi experimental design" by design "non equivalent control group". This research was conducted at STIKES Payung Negeri Pekanbaru on 34 people with 17 people as experimental group and another 17 people as control group with a purposive sampling technique. Measuring instrument used questionnaire Zung Self-Rating Anxiety Scale. Laughter therapy was given to experimental group as many as once prior to the evaluation study carried out for 20-30 minutes. The analysis used univariate analysis to determine the frequency distribution and bivariate usedDependent testof t test and Independent t tests. The results showed the differences in anxiety levels significantly after being given laughter therapy between the experimental group and the control group with p value = 0.000 <(0.05). It could be concluded that laughter therapy was effective one  decrease in the level of anxiety. The results of this study were expected to be one of the nursing interventions to reduce the level of student’s anxiety in the face of learning evaluation. Keywords: Anxiety, laughter therapy, Zung Self-Rating Anxiety Scale